The association between smoking and smokeless tobacco use with dental caries among Pakistani patients - Muhammad Azad Khan; Tippanart Vichayanrat; Yaowaluk Ngoenwiwatkul (BMC, 2024)
Abstract Background Tobacco use is widely recognised as a significant risk factor for oral cancer and periodontal diseases. However, the relationship between various types of tobacco use and dental caries has been inconsistent. This study aimed to determine the association between smoking and smokeless tobacco and dental caries among patients in a tertiary care hospital in Quetta, Pakistan. Methods This cross-sectional study was conducted from November 2020 to March 2021 among patients in a tertiary care hospital in Quetta, Pakistan. Oral examinations and interviews were performed according to the WHO Oral Health Survey basic methods (5th edition) to determine dental caries status, tobacco use, and oral health behaviours. The odds ratio and binary logistic regression were analysed to assess the association between the types (smoking tobacco, smokeless tobacco, and use of both types), duration, and frequency of tobacco use and high caries level (DMFT ≥ 5). Results Four hundred participants aged 18-65 were included, and 67.8% were tobacco users. Use of both smoking and smokeless tobacco (aOR = 14.7, 95%CI = 1.87-115.96, p = 0.011), smokeless tobacco only (aOR = 5.90, 95%CI = 1.89-18.37, p = 0.002), and smoking only (aOR = 2.18, 95%CI = 1.23-3.88, p = 0.008) were associated with significantly increased risk of high caries. Using tobacco for longer periods and more frequently daily also significantly increases the risk of high caries. Conclusion Smoking and smokeless tobacco are significantly associated with high dental caries after adjusting for other factors. Due to the high severity of dental caries and the high prevalence of tobacco use among Pakistani patients in this study, it is highly recommended to strengthen policies aimed at reducing tobacco usage, including smokeless forms.